White Crocodile as Social Criticism of Polygamy Phenomenon in Curug Dahu Village - Yuda Syah Putra; Irpan Riana (Universitas Pasundan, 2022)
The purpose of this study was to analyze the structure of the traditional wedding ceremony and the White Crocodile performance in Curug Dahu Village. Signifying the concept of denotation and connotation of the White Crocodile in the traditional wedding ceremony in Curug Dahu Village, and analyzing the relationship between the White Crocodile communication elements to the phenomenon of polygamy in the Curug Dahu village. The research method used is a qualitative research method. The data collection technique was carried out starting with literature study, observation and interviews accompanied by documentation. The object of this research is the White Crocodile in a Sundanese traditional ceremony in Curug Dahu Village. This research uses Roland Barthes' Semiotics theory. Decoding the codes and identifying the denotations that have been formed are obtained at the primary level (denotation), Keywords: White Crocodile, Social Criticism, Polygamy, Roland Barthes